Virtual Screening on MMP-13 Led to Discovering New Inhibitors Including a Non-Zinc Binding and a Micro Molar One: A Successful Example of Receptor Selection According to Cross-Docking Results for a Flexible Enzyme - Ramezani, Mohammad; Shamsara, Jamal (Combinatorial Chemistry & High Throughput Screening, 2017)
Aim and Objective: MMP-13 belongs to a large family of proteases called matrix metalloproteinases (MMPs) that degrades type II collagen, the main structural protein of articular cartilage. The main pathologic role of MMP-13 over expression is to contribute to the development of osteoarthritis. Methods: To find new inhibitors with possible selectivity for MMP-13 a structure based virtual screening was employed. The inhibitory activities of 11 inhibitors among 19 purchased compounds were approved by enzyme inhibition assay. Results: Our results demonstrated that the CADD (computer aided drug design) could be successfully applied to find new MMP-13 inhibitors using a receptor structure (PDB code: 3O2X) which had been demonstrated a good performance in a cross-docking study. Conclusion: We discovered inhibitors with new scaffolds for inhibition of MMP-13 and some selectivity features such as proper S1′ occupancy and interactions with S1′ pocket that could be subjected to a future lead optimization study.
Keywords: matrix metalloproteinase